Gambaran Pelaksanaan Patient Safety Di Ruang IBS (Instalasi Bedah Sentral) RSUD Brebes - Azkiyah, Isnaeni Maulina; Suandika, Made; Yudono, Danang Tri (Jurnal Ilmiah Wahana Pendidikan, 2024)
The impact of inaccurate diagnosis codes is a decrease in the quality of hospital services, payment of INA-CBG's tariff claims that will hamper payment, inaccurate morbidity, mortality, and hospital statistics reports. The research was conducted at RSIJ Cempaka Putih. The purpose of this study was to identify the SPO of disease and action codes, analyze the accuracy of the diagnosis code of pulmonary tuberculosis disease for inpatients, and identify the causes of inaccurate diagnosis codes of pulmonary tuberculosis disease for inpatients. The research method used was descriptive method with quantitative approach. The population amounted to 658 medical records with a sample of 96 medical records. The sample was determined using the slovin formula. SPO for diagnosis and action coding has generally been running. The results showed that there were 46 medical records (48%) with the correct diagnosis code, 25 medical records (26%) with incorrect 3rd digit, 20 medical records (21%) with incorrect 4th digit, 5 medical records (5%) with incorrect 3rd digit and 4th digit. Factors causing inaccurate diagnosis codes are found in the man factor, in this case the coder does not pay attention to the accuracy of the notes detailing the accuracy of coding in ICD-10. Material factors, the unavailability of coding tools such as medical dictionaries and ICD-10 books. Method factors, the SPO has not specifically described the steps of how to code.